2019
DOI: 10.1186/s12889-019-6805-2
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol of the X:IT II - a school-based smoking preventive intervention

Abstract: Background The X:IT intervention, conducted in 2010 to 2013, showed overall smoking preventive effect. However, parts of the intervention appeared less appealing to children from families with lower socioeconomic backgrounds. Therefore, the intervention components were modified and an evaluation of the amended intervention X:IT II is needed to show the effect of this revised intervention and whether children from different social backgrounds benefits equally from the current intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Generally, individuals with a lower socioeconomic position are more likely to start smoking in adolescence and less likely to quit smoking in adulthood [ 1 , 2 ]; thus, contributing to social disparities in smoking and in health. An increasing priority of smoking preventive measures is to equalize socioeconomic disparities in smoking [ 3 , 4 ]. However, these efforts might be challenged because health interventions are sometimes easier adopted by individuals from higher socioeconomic backgrounds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, individuals with a lower socioeconomic position are more likely to start smoking in adolescence and less likely to quit smoking in adulthood [ 1 , 2 ]; thus, contributing to social disparities in smoking and in health. An increasing priority of smoking preventive measures is to equalize socioeconomic disparities in smoking [ 3 , 4 ]. However, these efforts might be challenged because health interventions are sometimes easier adopted by individuals from higher socioeconomic backgrounds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used data from the X:IT II intervention, a multi-component intervention aiming at preventing smoking uptake among adolescents in the school (3). The Danish Cancer Society developed the intervention and its effectiveness was evaluated by the Centre for Intervention Research, University of Southern Denmark in the period from September 2017 until June 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, individuals with a lower socioeconomic position are more likely to start smoking in adolescence and less likely to quit smoking in adulthood (1,2); thus, contributing to social disparities in smoking and in health. An increasing priority of smoking preventive measures is to equalize socioeconomic disparities in smoking (3,4). However, these efforts might be challenged because health interventions are sometimes easier adopted by individuals from higher socioeconomic backgrounds (5).…”
Section: Introductionmentioning
confidence: 99%
“…As far as quitting smoking behavior is concerned, several studies at home and abroad that have found that self-efficacy is related significantly to quitting smoking. [ 13 16 ] Therefore, in this study, self-efficacy is listed as an important variable with the hope of reconfirming that self-efficacy has an important influence on quitting smoking behaviors of people who quit smoking in clinics.…”
Section: Introductionmentioning
confidence: 92%